Overcoming barriers to HPV vaccination in rural Vermont through a multicomponent peer-based approach - Finlay Pilcher; Jan Kirk Carney; Gary S. Stein (Human Vaccines & Immunotherapeutics, 2022)
Human Papillomavirus (HPV) causes almost all cervical cancers and many cancers of the anus, vagina, vulva, penis, and oropharynx. The HPV vaccine provides protection to all adolescents from a broad spectrum of cancers, yet HPV vaccination rates remain lower than those of other routine vaccines. Developing effective HPV vaccine interventions is particularly important in rural areas, whose residents have lower rates of HPV vaccination and higher cervical cancer incidence and mortality; however, interventional research in these populations is relatively limited. Furthermore, though rural areas are heterogeneous in many regards, few interventions engage stakeholders to develop community-specific solutions to overcome obstacles associated with HPV vaccination. Based on a review of existing literature, we recommend a multicomponent peer-based approach that includes school-based vaccination and awareness, parental involvement, and stakeholder engagement to increase HPV vaccination in rural areas, and we provide an example of such an intervention in rural Vermont.